Autosomal locus regulates inverse relationship between sialic acid content and capacity of mouse erythrocytes to activate human alternative complement pathway - Nydegger, Urs E. (1978)
The observation that mouse erythrocytes (E(m)) from 21 inbred strains had variable capabilities to activate the human alternative complement pathway permitted the demonstration that membrane sialic acid content was inversely related to activating capacity and was regulated by codominant alleles of a single autosomal locus. Linear regression analysis also demonstrated a significant inverse correlation between the sialic acid content of E(m) from four inbred strains and the concentration of β1H required for decay-dissociation of the properdin-stabilized amplification convertase on the E(m). E(m) from F(1) hybrids derived from strains with high and low alternative pathway activating capacities and from their backcrosses exhibited the alternative pathway activating capacities expected if the activity were regulated by alleles of a single autosomal locus. That this same locus predominantly regulated the sialic acid content of E(m) was established by the significant inverse correlation between the sialic acid content and the alternative pathway activating capacity of E(m) from mice of the F(1) and backcross generations. Although the fluid phase interaction of C3, B, and [unk]D continuously generates C3b in a reaction augmented by properdin, it is the covalent attachment of C3b to bystander surfaces deficient in sialic acid that activates the alternative complement pathway at that site because of impaired binding of β1H to C3b on such surfaces. Thus, discrimination between activating and nonactivating surfaces occurs after C3b deposition, and sialic acid deficiency represents the molecular basis for our earlier finding that activating particles circumvent the regulatory actions of the control proteins of the alternative pathway.